Towards a UML Profile for the Simulation Domain - Mourad, Maouche; Mohamed, Bettaz (Informatica, 2019)
Model driven approaches have recently been exploited to implement simulation systems. Most of the reported contributions have adopted the Model Driven Architecture (MDA), a model driven approach widely used in software engineering. Simulation Platform Description Models (SPDM), which are first citizens MDA models intended for the description of simulation platforms supporting the execution of simulation experiments , are not explicitly considered in the previous works. The purpose of this work is to define a UML profile intended for the modeling of both simulation core concepts and simulation platforms. The contribution of this work is threefold: First we review and synthesize recent contributions in modeling and simulation approaches, practices and platforms; second we propose a resource-oriented approach for the modeling of simulation platform elements; third we consider both component- and workflow-based simulation platforms.